SHEAR STRENGTH MEASUREMENT OF MINERAL FILTER CAKES - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2010)
The shear strength of filter cakes of dolomite and quartz minerals was measured using a uni-axial test apparatus which was designed in the laboratory. For this aim a uni-axial button pressing machine used in textile industry was modified and used to measure the shear strength of dolomite and quartz pressure filter cakes with satisfying results. The results obtained with this machine were compared and found as in good agreement with the results of industrial devices, Fisher test apparatus and Universal Sand Strength Machine.
Keywords: Shear strength; Uni-axial test apparatus; Filtration; Filter cakes; Dolomite; Quartz; PARTICLE-SHAPE; PRESSURE; FILTRATION; BEHAVIOR; FLOW; SIZE